European consensus-based interdisciplinary guideline for melanoma. Part 1: Diagnostics: Update 2022 - Garbe, Claus; Amaral, Teresa; Peris, Ketty; Hauschild, Axel; Arenberger, Petr; Basset-Seguin, Nicole; Bastholt, Lars; Bataille, Veronique; Del Marmol, Veronique; Dréno, Brigitte; Fargnoli, Maria C; Forsea, Ana-Maria; et al. (European journal of cancer (Oxford, England, 2022)
Cutaneous melanoma (CM) is potentially the most dangerous form of skin tumor and causes 90% of skin cancer mortality. A unique collaboration of multi-disciplinary experts from the European Dermatology Forum (EDF), the European Association of Dermato-Oncology (EADO) and the European Organization for Research and Treatment of Cancer (EORTC) was formed to make recommendations on CM diagnosis and treatment, based on systematic literature reviews and the experts' experience. The diagnosis of melanoma can be made clinically and shall always be confirmed with dermatoscopy. If a melanoma is suspected, a histopathological examination is always required. Sequential digital dermatoscopy and full body photography can be used in high-risk patients to improve the detection of early melanoma. Where available, confocal reflectance microscopy can also improve clinical diagnosis in special cases. Melanoma shall be classified according to the 8th version of the American Joint Committee on Cancer classification. Thin melanomas up to 0.8 mm tumor thickness do not require further imaging diagnostics. From stage IB onwards, examinations with lymph node sonography are recommended, but no further imaging examinations. From stage IIC onwards whole-body examinations with computed tomography (CT) or positron emission tomography CT (PET-CT) in combination with brain magnetic resonance imaging are recommended. From stage III and higher, mutation testing is recommended, particularly for BRAF V600 mutation. It is important to provide a structured follow-up to detect relapses and secondary primary melanomas as early as possible. There is no evidence to define the frequency and extent of examinations. A stage-based follow-up scheme is proposed which, according to the experience of the guideline group, covers the optimal requirements, but further studies may be considered. This guideline is valid until the end of 2024.
Keywords: Cutaneous melanoma; Total body photography; nádory kůže; Consensus; Humans; Skin Neoplasms; Melanoma, Cutaneous Malignant; melanom; Sequential digital dermatoscopy; Imaging diagnostics; lidé; Mutation testing; maligní melanom kůže; konsensus; Dermatoscopy; staging nádorů; Follow-up examinations; AJCC classification; Positron Emission Tomography Computed Tomography; Melanoma; Primary diagnosis; Neoplasm Staging; lokální recidiva nádoru; Neoplasm Recurrence, Local; PET/CT; Confocal reflectance microscopy